Exploring the Role of Counting Box Media in Supporting Elementary Students’ Understanding of Addition Concepts - Khoirul, Maghfiriyah; Sukartono, Sukartono (Jurnal Pendidikan Matematika dan Sains, 2026)
This study aims to describe the role of the counting box media in learning addition in first grade, identifying obstacles, supporting factors, and solutions to these obstacles. The study used a descriptive qualitative method with a phenomenological design through interviews, observations, and documentation with teachers and first-grade students at an Islamic elementary school in Boyolali. The results show that counting box media helps students understand the concept of addition through concrete experiences, making learning more enjoyable, encouraging active participation, increasing motivation, and making the learning process more meaningful. Obstacles include limited media, inadequate components, and an unconducive classroom environment. Solutions to overcome these obstacles include increasing the number of media, providing additional questions, adjusting the number of magnets, and adding pom-poms to make the media more effective. The implications of this study indicate that the use of the Counting Box media contributes to the achievement of the SDGs through effective and inclusive addition learning and the development of similar media for other arithmetic operations.